A Test of Energetic Particle Precipitation Models Using Simultaneous Incoherent Scatter Radar and Van Allen Probes Observations. Issue 8 (10th August 2022) - Sanchez, Ennio R.; Ma, Qianli; Xu, Wei; Marshall, Robert A.; Bortnik, Jacob; Reyes, Pablo; Varney, Roger; Kaeppler, Stephen
Abstract: Quantification of energetic electron precipitation caused by wave‐particle interactions is fundamentally important to understand the cycle of particle energization and loss of the radiation belts. One important way to determine how well the wave‐particle interaction models predict losses through pitch‐angle scattering into the atmospheric loss cone is the direct comparison between the ionization altitude profiles expected in the atmosphere due to the precipitating fluxes and the ionization profiles actually measured with incoherent scatter radars. This paper reports such a comparison using a forward propagation of loss‐cone electron fluxes, calculated with the electron pitch angle diffusion model applied to Van Allen Probes measurements, coupled with the Boulder Electron Radiation to Ionization model, which propagates the fluxes into the atmosphere. The density profiles measured with the Poker Flat Incoherent Scatter Radar operating in modes especially designed to optimize measurements in the D‐region, show multiple instances of close quantitative agreement with predicted density profiles from precipitation of electrons caused by wave‐particle interactions in the inner magnetosphere, alternated with intervals with large differences between observations and predictions. Several‐minute long intervals of close prediction‐observation approximation in the 65–93 km altitude range indicate that the whistler wave‐electron interactions models are realistic and produce precipitation fluxes of electrons with energies between 10 keV and >100 keV that are consistent with observations. The alternation of close model‐data agreement and poor agreement intervals indicates that the regions causing energetic electron precipitation are highly spatially localized. Plain Language Summary: Establishing how electromagnetic waves in the magnetosphere push high‐energy electrons into a funnel directed toward Earth along magnetic field lines is a critically important step to predict how electrons are lost into the atmosphere during geomagnetic storms. Wave‐electron interaction models predict the number of electrons that are funneled toward Earth from a set of in‐situ spacecraft measurements. As the electrons hurl into the upper atmosphere, ionization models predict how many electrons would be released by the neutral atmosphere due to the bombardment from funneled electrons. Electron density measurements with a radar especially tuned to optimize detection of electron densities in the upper atmosphere can be compared to predicted electron densities to determine the validity of the electron loss models. This paper reports a comparison for an interval of time when a Van Allen Probes spacecraft is measuring the waves and electrons at a location that would guarantee that the electrons would fall near the radar's location in Poker Flat, Alaska. The comparison shows that the models considered predict the correct number of electrons in multiple instances, thus establishing an important step in verifying the validity of the models of electron loss during geomagnetic storms. Key Points: Comparison between observed and modeled density for electron precipitation due to wave‐particle interactions in the magnetosphere Comparison verifies the validity of D‐region electron density predicted by pitch‐angle diffusion models of wave‐particle interaction Observed electron profiles are obtained with an incoherent scatter radar mode especially designed to optimize measurements in the D‐region